PENGGUNAAN MAJAS DALAM TEKS CERPEN SISWA KELAS XI SMA NEGERI 2 PAYAKUMBUH - Anisyah, Fitri; Gani, Erizal; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT The objectives of this study were to describe (1) the types of masters found, (2) the types of majas that emerged, (3) the slightly emerging type of masters, (4) knowing the types of majas that never appeared, (5) the short story text students of SMAN 2 Payakumbuh class XI. The data in this study is the masters which is contained in the text of the students of the class XI SMAN 2 Payakumbuh. the source of this research data is an official document in the from of the text clusters of students class XI MIPA 3 SMAN 2 Payakumbuh which is collected and archived by Indonesian teachers semester one academic year 2017/2018. Data were collected using documentation study. Based on the result of the research, it can be concluded that (1) found 13 types of masters used; (2) the emerging masters are hyperbolic masters; (3) the slightly emerging masters are antitheses, litotes, paralipsis, zeugma, metonimia, allusions, and inversions; (4) the types of majas that never arise are allegory, irony, paranomasia, sinekdoke, euphemism, ellipsis, gradation, alliteration, antanaclasis, and kiasmus; and (5) there are findh seven atmosphere of appearance of majas in the text of short story of student of class XI SMAN 2 Payakumbuh. Kata kunci: teks cerpen, majas, suasana